Congenital subcostal hernia in a patient with Lumbo-Costovertebral Syndrome, case report and review of the literature - Colin Muncie; Christopher Ng; Henry Giles; Christopher Blewett (Elsevier, 2016)
Congenital subcostal hernias are a very rare type of flank hernia. They are typically asymptomatic but are more difficult to fix as the child grows, warranting early repair. They are typically found in the setting of multiple congenital anomalies. We report a congenital subcostal hernia associated with Lumbo-Costovertebral Syndrome, which is already known to be associated with congenital lumbar hernias. We will report the background and outcome of primary repair in such a hernia.